THE U.S. VS RUSSIA IN MILITARY-POLITICAL COOPERATION WITH TAJIKISTAN - STARCHAK, Maksim (CENTRAL ASIA AND THE CAUCASUS, 2009)
Tajikistan, which has a 1,200-km-long border with Afghanistan, was in demand during Operation Enduring Freedom. At the beginning of 2002, Tajikistan opened its air corridor to NATO’s military transport aircraft and 250 French servicemen were deployed at the civilian airport in Dushanbe. The United States was allowed to use the Dushanbe and Kulob aerodromes for deploying its contingents.1 American congressmen, senators, ministers, and the heads of military departments began paying more frequent visits to the republic.The republic, which borders directly on Afghanistan, was hoping for military-technical assistance in the fight against terrorism and drug trafficking. This hope was encouraged when U.S. Congress cancelled the embargo on arms deliveries to Tajikistan. However, the U.S. did not ask Tajikistan for permission to deploy its bases in the country. This was partly because, after taking a look at Kulob (a former Soviet base), the U.S. Central Command deemed it insufficiently equipped and too small,2 although it could have provided the best access to the strategically important Pansher Valley. Moreover, Dushanbe could not respond in any way without first resolving the problem of Russia’s military base, talks on which began back in 1999. However, the country’s president, Emomali Rakhmon, was potentially in favor of deploying the American military base provided it brought economic benefit.But the Americans did not want to have their military bases right next to the 201st Russian division. Nevertheless, American experts did call on the U.S. to deploy operational structures in Tajikistan in order to increase control over drug trade and support the American forces in Afghanistan in the event the Taliban or other anti-Western Islamic groups became further entrenched there.